Emerging Roles of Platelets in Allergic Asthma - Yue, Ming; Hu, Mengjiao; Fu, Fangda; Ruan, Hongfeng; Wu, Chengliang (Frontiers in Immunology, 2022)
Allergic asthma is a complex chronic inflammatory disease of the airways, driven by Th2 immune responses and characterized by eosinophilic pulmonary inflammation, airway hyperresponsiveness, excessive mucus production, and airway remodeling. Overwhelming evidence from studies in animal models and allergic asthmatic patients suggests that platelets are aberrantly activated and recruited to the lungs. It has been established that platelets can interact with other immune cells and secrete various biochemical mediators to promote allergic sensitization and airway inflammatory response, and platelet deficiency may alleviate the pathological features and symptoms of allergic asthma. However, the comprehensive roles of platelets in allergic asthma have not been fully clarified, leaving attempts to treat allergic asthma with antiplatelet agents questionable. In this review, we summarize the role of platelet activation and pulmonary accumulation in allergic asthma; emphasis is placed on the different interactions between platelets with crucial immune cell types and the contribution of platelet-derived mediators in this context. Furthermore, clinical antiplatelet approaches to treat allergic asthma are discussed. This review provides a clearer understanding of the roles of platelets in the pathogenesis of allergic asthma and could be informative in the development of novel strategies for the treatment of allergic asthma.